CONSIDERAÇÃ•ES SOBRE O NÚMERO DE PLUVIÃ”METROS NECESSÃRIOS EM EXPERIMENTOS DE BALANÇO HÃDRICO DE CAMPO - Bruno, Isabeli Pereira; Reichardt, Klaus; Silva, Adriana Lúcia da; Volpe, Clóvis A.; Timm, Luis Carlos; Bacchi, Osny Oliveira Santos; Dourado Neto, Durval; Piedade, Sônia Maria de Stefano; Oliveira, Júlio César Martins de (REVISTA DE AGRICULTURA, 2015)
CONSIDERAÇÃ•ES SOBRE O NÚMERO DE PLUVIÃ”METROS NECESSÃRIOS EM EXPERIMENTOS DE BALANÇO HÃDRICO DE CAMPO